Peeling back the layers of learning: a classroom model for problem-based learning. - McLoughlin M; Darvill A (Nurse Education Today, 2007)
This paper aims to provide an informative discussion with underpinning rationales about the use of a problem-based learning (PBL) classroom model, supported by a structured process for undertaking PBL. PBL was implemented as a main teaching and learning strategy for a diploma in nursing programme as advised by the Department of Health [Department of Health., 1999. Making a difference: Strengthening the Nursing, Midwifery and Health Visiting Contribution to Health and Health Care. Department of Health, London.] and the United Kingdom Central Council for nurses, midwifes and health visitors [United Kingdom Central Council for Nursing, Midwifery and Health Visiting, 1999. Fitness for Practice. UKCC, London.]. The implementation and change to the PBL approach is not without challenges, and so it was considered important to facilitate this change effectively. Through ongoing reflection, peer discussions and continuous review of the literature following studies at Masters Level, it was identified that the design of a model may guide students and facilitators who were new to the PBL process to help students identify relevant learning needs and thus enable them to achieve the learning outcomes of a dynamic curriculum [Darvill, A., 2000. Developing Problem-based Learning in the Nursing Education Curriculum: A Case Study. Unpublished MSc Dissertation, University of Huddersfield, Huddersfield; McLoughlin, M., 2002. An Exploration of the Role of the Problem-based Learning Facilitator: An Ethnographic Study of Role Transition in a Higher Education Institution 'Paradigm Shift or New Ways of Working'. Unpublished MSc Dissertation. University of Huddersfield, Huddersfield.]. In this paper the key components of the model will be described.